Towards an understanding of Chinese business networks in Asia-Pacific: The Singapore case - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 1995)
The embeddedness of entrepreneurs in local, regional or global business networks based on kinship, clanship, territorial or ethnic ties and solidarities has often been cited as characteristic of the Chinese business community in Southeast Asia. Qualitative interviews with Singaporean Chinese merchant-exporters were conducted in order to examine this thesis and shed light on the various "guanxi bases" of their international trading networks. The findings suggest that there is a strong tendency among these Singaporean entrepreneurs towards external commercial transactions with "outsiders" and "friends" rather than with "kin" whether by blood, marriage, or ascription. Kinship reciprocity may curb the autonomy and freedom of choice of these actors, limiting their economic options in regional and international marketplaces.